1995
DOI: 10.1007/bf01276462
|View full text |Cite
|
Sign up to set email alerts
|

?-CIT SPECT demonstrates blockade of 5HT-uptake sites by citalopram in the human brain in vivo

Abstract: The cocaine analogue 2-beta-carbomethoxy-3-beta-(4-iodophenyl)-tropane (beta-CIT) is a potent ligand for both dopamine- and serotonin uptake sites which in its 123I labeled form can be used for single photon emission computerized tomography (SPECT). It was demonstrated previously by SPECT-studies in non-human primates that 123I-beta-CIT binds to dopamine transporters in the striatum and to serotonin transporters in hypothalamus and midbrain. The aim of the present study was to compare 123I-beta-CIT binding in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
76
2

Year Published

2001
2001
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 123 publications
(78 citation statements)
references
References 20 publications
0
76
2
Order By: Relevance
“…As the differences were small and because several studies reported stable uptake in the (hypo)thalamus, midbrain, cerebral cortex, and cerebellum at 4 h p.i. (Brücke et al, 1993;Pirker et al, 1995), it was suggested that both time points are reliably for measurements of SERTs with [ 123 I]b-CIT (Pirker (Pirker et al, 1995;Kugaya et al, 2003). Human PET studies using the SERT-selective radiotracer [ 11 C]DASB also showed high occupancy of SERTs in the midbrain and thalamus after (sub)therapeutic doses of various SSRIs (Meyer et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As the differences were small and because several studies reported stable uptake in the (hypo)thalamus, midbrain, cerebral cortex, and cerebellum at 4 h p.i. (Brücke et al, 1993;Pirker et al, 1995), it was suggested that both time points are reliably for measurements of SERTs with [ 123 I]b-CIT (Pirker (Pirker et al, 1995;Kugaya et al, 2003). Human PET studies using the SERT-selective radiotracer [ 11 C]DASB also showed high occupancy of SERTs in the midbrain and thalamus after (sub)therapeutic doses of various SSRIs (Meyer et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that [ 123 I]b-CIT binding in the cerebral cortex is predominantly caused by binding to SERTs. However, other studies were not able to show that [ 123 I]b-CIT binds to cortical SERTs (Laruelle et al, 1993) or did not study this issue (Pirker et al, 1995;Kugaya et al, 2003). In addition, a SSRI displacement study with the SERT-selective PET radioligand [ 11 C]McN 5652 in nonhuman primates also failed to show specific binding in the cerebral cortex (Parsey et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations